Controlling factor analysis of oceanic surface pCO2 in the South China Sea using a three-dimensional high-resolution biogeochemical model - Zhang, Miaoyin; Zhu, Xueming; Ji, Xuanliang; Zhang, Anmin; Zheng, Jingjing (Frontiers in Marine Science, 2023)
The oceanic surface pressure of CO2 (pCO2) is an essential parameter for understanding the global and regional carbon cycle and the oceanic carbon uptake capacity. To compensate for the limitation of observation coverage spatially and temporally, a three-dimensional physical-biogeochemical model with a high resolution of 1/30° is constructed for the South China Sea (SCS) to represent and simulate oceanic surface pCO2 from 1992 to 2021 for a better understanding of the seasonal and interannual variations of oceanic surface pCO2 in this region. The model results show that SCS serves as an atmospheric CO2 source from March to October and a sink from November to February with a domain-averaged climatological oceanic surface pCO2 value varies between 357 and 408 μatm, and the temporal variation is positively correlated with the variation of sea surface temperature (SST). The majority of the SCS shows a long-term increasing trend for oceanic surface pCO2 with a value of (1.19±0.60) μatm/a, which is in response to the continuously rising atmospheric CO2 concentration. By conducting the empirical orthogonal function analysis (EOF) on deseasonalized and detrended oceanic pCO2, it is found that PC1 shows a good response to the Niño 3 index with a correlation coefficient of 0.51 when the Niño 3 leading 5 months, and PC2 is correlated with the PDO index when the PDO leading 7 months, which suggests an influence of climate variability on the carbonate system. Moreover, it is found that the long-term trend rate of oceanic surface pCO2 is mainly controlled by total CO2 (TCO2) through decomposition of influence factors, and SST variation takes a dominant role in seasonal variations of pCO2. With rapid global warming and continuous release of CO2, the carbonate system in the SCS may change leading to calcite and aragonite saturation.